Digital Marketing and Product Quality Shape Perfume Purchase Decisions - Della Sari; Indah Respati Kusumasari (Academia Open, 2025)
(General Background) In the era of Industry 4.0, digital marketing has become a transformative force that reshapes how businesses communicate and engage with consumers. (Specific Background) Within Indonesia’s perfume industry, local brands such as SAFF & Co face growing competition and rely heavily on digital strategies to build brand awareness and influence consumer behavior. (Knowledge Gap) However, limited research has explored how digital marketing and perceived product quality simultaneously affect consumer purchase intention in the context of local perfume brands. (Aims) This study aims to analyze the effect of digital marketing and perceived product quality on purchase intention for SAFF & Co perfume in Surabaya. (Results) Using a quantitative approach with 100 purposively selected respondents and multiple linear regression analysis, the findings reveal that both digital marketing and perceived product quality have a significant positive effect on purchase intention, with digital marketing having a stronger influence (R² = 0.409). (Novelty) This study highlights the dominance of digital marketing as a driver of purchase intention in the local perfume sector, emphasizing its role in creating virtual consumer experiences where sensory evaluation is limited. (Implications) The results imply that effective digital marketing strategies and consistent product quality are essential for enhancing consumer trust and purchase intention in digital marketplaces. Highlights: Shows digital marketing’s strong influence on perfume purchase intention. Identifies product quality as a key factor strengthening consumer trust. Reveals digital engagement explains 40.9% of purchase intention variance. Keywords: Digital Marketing, Product Quality, Purchase Intention, Consumer Behavior, Perfume Industry